The emerging historical site as a tourism destination in Bongan village, Bali - Sunarta, I Nyoman; ., Nuruddin; Kristianto, Yohanes (Opción, 2019)
This study aims to identify the potencies of the cultural heritage of Bongan Village, Bali Indonesia, which has not been commodified as part of a tourism destination and at the same time as the preservation of historical heritage. This study uses a qualitative approach by focusing on participant observation and in-depth interviews. The results indicate that there are two emerging perspectives of developing tourism village both cultural heritage tourism and preservation of historical sites. In conclusion, cultural heritage can support the concept of a tourist village that is being promoted, it is necessary to improve some of the sectors.